The Impact Of Internet Embeddedness On Resource Identification —— The Mediators Role Of Enterpreneurial Learning - Li, Jianing (2024)
With the development and application of internet technology, more and more entrepreneurs obtain entrepreneurial resources through the internet to carry out entrepreneurial activities. Resource identification is the key to the growth of new startups. In the process of entrepreneurship, entrepreneurs must solve the problem of how at what cost, and where to obtain resources. According to the characteristics of resources and the stage of enterprise development, entrepreneurs can use different identification methods to finally identify the required resources and then obtain resources, which lays the foundation for the further development of enterprises. In the process of resource identification, rich knowledge is needed, and the source of this knowledge is entrepreneurial learning. Through entrepreneurial learning, entrepreneurs will transform their entrepreneurial knowledge into their abilities, improve their resource identification ability, and lay a good foundation for the resource integration of future entrepreneurial activities.The theoretical framework of this study is based on upper echelons theory and the concepts of internet embedding, resource identification, and entrepreneurial learning. During the research process, internet embedding was divided into three dimensions: connect degree, matching degree, and sense of sacrifice. The closer the connection between individuals and the internet, the higher the degree of matching between the internet and individual needs, and the more objects individuals face from the internet, the deeper their degree of embedding.